Theoretical study of the ionization of liquid water from its several initial orbitals by fast electron impact - de Sanctis, Maria Laura (2015)
We theoretically study the single ionization of liquid water by energetic electrons through one active-electron first-order model. We analyze the angular ejected electron spectra corresponding to the most external orbitals 1B1, 2A1, 1B2 and 1A1 of a single water molecule. We work to create a realistic description of those orbitals corresponding to single molecules in the liquid phase. This goal is achieved by means of a Wannier orbital formalism. Multiple differential cross sections are computed and compared with previous calculations for both liquid and gas phases. In addition, our present results are integrated over all orientations and compared with experimental ones for randomly oriented vapour water molecules, as no experiments currently exist for the liquid phase. Moreover, we estimate the influence of the passive electrons on the reaction by means of a model potential.